Philosophy And Implementation of Qardh Contracts In Islamic Banks In Indonesia - Aravik, Havis; Tohir, Ahmad (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2025)
This study examines the philosophy and implementation of qardh contracts in Islamic banks in Indonesia, which are normatively positioned as tabarru' contracts oriented towards social welfare. However, in practice, qardh contracts often undergo a shift in meaning when they are used as an additional instrument to support liquidity or as a complementary banking product. This condition creates a gap between the normative ideal of qardh as a social instrument and the reality of its implementation, which is often influenced by the business logic of financial institutions. The purpose of this study is to analyse in depth the philosophical and implementational dimensions of qardh contracts and to identify the gap between basic sharia values and contemporary banking practices. The research method used is qualitative with a descriptive-analytical approach. Primary data was obtained through interviews with practitioners, academics, and regulators, while secondary data was sourced from DSN-MUI fatwas, OJK regulations, Islamic bank reports, and academic literature. The analysis was conducted using content and thematic analysis methods. The results of the study show that qardh has a strong philosophical basis as a tabarru' contract that emphasises justice and social solidarity, but its implementation is often reduced by the demands of commercialisation and limited incentives. This study confirms the dual function of qardh, namely as a social instrument for community empowerment and as a technical instrument for banking liquidity. These findings recommend innovative strategies to ensure that qardh remains relevant and sustainable within the Islamic banking system.